Pengenalan Virtual Reality untuk Meningkatkan Kreativitas Multimedia bagi Siswa-Siswi SMK Telkom Pekanbaru - Efendi, Yoyon; Nasution, Torkis; Nurjayadi, Nurjayadi; Fatdha, T Sy Eiva; Gunadi, Gunadi (Community Education Engagement Journal, 2024)
The development of information and communication technology (ICT) is currently very rapid and dynamic, leading to advanced products that are highly sought after by the global community. Innovations in ICT have permeated various fields, including education, through the integration of flexible technology-based learning media that can be accessed anytime and anywhere. One of the advancements in multimedia in education is Virtual Reality (VR), which allows for deep interaction with digital objects in a virtual reality environment. VR can simulate an ideal environment with intense visual and auditory stimulation. SMK Telkom in Pekanbaru, which offers various vocational programs, currently only implements ICT-based education at a basic level, limited to theory and practice. To enhance creativity in the teaching and learning process, innovative solutions are needed, such as the application of VR-based multimedia technology. This training aims to introduce VR as a tool to improve the learning outcomes and achievements of students at SMK Telkom Pekanbaru. Problem identification reveals that the teaching and learning activities are not fully ICT-based, there is a lack of information regarding multimedia, and limited innovation can affect learning effectiveness. Therefore, the community service team formulated the problem of how the introduction of VR can enhance multimedia creativity and learning outcomes at SMK Telkom Pekanbaru.